Chondrogenic Differentiation of Human Mesenchymal Stem Cells via SOX9 Delivery in Cationic Niosomes - Natalia Carballo-Pedrares; Clara Sanjurjo-Rodriguez; Jose Señarís; Silvia Díaz-Prado; Ana Rey-Rico (MDPI AG, 2022)
Gene transfer to mesenchymal stem cells constitutes a powerful approach to promote their differentiation into the appropriate cartilage phenotype. Although viral vectors represent gold standard vehicles, because of their high efficiency, their use is precluded by important concerns including an elevated immunogenicity and the possibility of insertional mutagenesis. Therefore, the development of new and efficient non-viral vectors is under active investigation. In the present study, we developed new non-viral carriers based on niosomes to promote the effective chondrogenesis of human MSCs. Two different niosome formulations were prepared by varying their composition on non-ionic surfactant, polysorbate 80 solely (P80), or combined with poloxamer 407 (P80PX). The best niosome formulation was proven to transfer a plasmid, encoding for the potent chondrogenic transcription factor SOX9 in hMSC aggregate cultures. Transfection of hMSC aggregates via nioplexes resulted in an increased chondrogenic differentiation with reduced hypertrophy. These results highlight the potential of niosome formulations for gene therapy approaches focused on cartilage repair.